Transforming Landscapes. Michel Desvigne Paysagiste. - (:unkn) unknown (Birkhäuser, 2020)
Michel Desvigne is the most renowned French landscape architect in the world. Based in Paris, he has held guest professorships at such distinguished institutions as the Architectural Association in London and Harvard University. Desvigne’s projects have a strong strategic and conceptual component. Urban infrastructure projects play a major role, and emphasize the urban planning and design expertise evident in his landscape architecture. The book documents ten of Devigne’s major projects from France, the US, Spain and Qatar, in which he is responsible not only for the landscape architecture, but for coordination of the entire project. How can such highly complex projects be realized? What does the intellectual thought process look like? What specific problems arise in their realization?
Keywords: Landschaftsarchitektur; Landschaftsarchitekt; Landschaftsgestaltung; Freiraumgestaltung; Ufergestaltung; Landschaftspark; Öffentlicher Raum; Umgestaltung; Stadterweiterung; Neubaugebiet; Projektauswahl